The new onset seropositive rheumatoid arthritis after COVID-19 infection: coincidental or related - (:unkn) unknown (MediHealth Academy, 2022)
Coronavirus disease 2019 (COVID-19) is an infectious disease, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The relationship of COVID-19 with rheumatological disorders has been researched since 2019. Rheumatoid arthritis (RA) is one of the most common rheumatoid diseases. The relationship between RA and COVID-19 is particularly interesting due to common cytokines in etiopathogenesis. SARS-CoV-2 was involved in triggering RF-positive and ACPA-positive arthritis, which might be diagnosed as rheumatoid arthritis, but we cannot rule out the possibility that the onset of this arthritis could have been coincidental. We report the case who has the first flare of RA with a high titer of Rheumatoid Factor (RF) and Anti Citrullinated Protein Antibody (ACPA) after mild SARS-CoV- 2 infection.
Keywords: 3. Good health